2019
DOI: 10.1007/s00381-019-04059-6
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association of cranial lacunae with intracranial hypertension in children with Crouzon syndrome and Apert syndrome: a 3D morphometric quantitative analysis

Abstract: Purpose Cranial lacunae (foci of attenuated calvarial bone) are CT equivalents of Bcopper beating^seen on plain skull radiographs in children with craniosynostosis. The qualitative presence of copper beating has not been found to be useful for the diagnosis of intracranial hypertension (IH) in these patients. 3D morphometric analysis (3DMA) allows a more systematic and quantitative assessment of calvarial attenuation. We used 3DMA to examine the relationship between cranial lacunae and IH in children with Crou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 19 publications
1
14
1
Order By: Relevance
“…To a certain extent, these complications have been solved by many studies to some degree. [16][17][18][19][20] Our study results support the claim that the base of the sphenoid bone is squeezed and cranial cavity is enlarged in patients with Crouzon syndrome and that the development of the cranial base and related facial features are significantly influenced by the major sutures. 13 These cranial deformities are likely due to the premature fusion of the cranial sutures, which limits the growth and developmental space for the brain tissue, leading to compression of the surrounding cranial base bones and the sphenoid part of the skull base, tending to be squeezed with papilledema.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…To a certain extent, these complications have been solved by many studies to some degree. [16][17][18][19][20] Our study results support the claim that the base of the sphenoid bone is squeezed and cranial cavity is enlarged in patients with Crouzon syndrome and that the development of the cranial base and related facial features are significantly influenced by the major sutures. 13 These cranial deformities are likely due to the premature fusion of the cranial sutures, which limits the growth and developmental space for the brain tissue, leading to compression of the surrounding cranial base bones and the sphenoid part of the skull base, tending to be squeezed with papilledema.…”
Section: Discussionsupporting
confidence: 85%
“…21 Meanwhile, some studies found that the ocular complications of Crouzon syndrome and the attenuation of cranial lacunae may not be related to ICP. 19,20 We consider that this is because the details of the ICP severity and how much space they obtained from the surgery varied much from patient to patient. We consider decompression to be necessary in most of the Crouzon syndrome patient.…”
Section: Discussionmentioning
confidence: 99%
“…There is also a debate regarding fingerprinting as a clinical sign of ICH. Several studies report a low sensitiviy to detect ICH [38][39][40][41][42]. However, a recent study has shown that fingerprinting resolves after surgical correction for ICH.…”
Section: Clinical Impactmentioning
confidence: 99%
“…6,14 It is essential to be well informed of the late-onset pansynostosis of CS, which occurs occasionally; because the slight distortion of the skull shape may disguise the presence of raised ICP. 11,13 Matter of Contention: Copper Beaten Skull: Copper beaten skull, also known as beaten silver skull or beaten brass skull, refers to the prominence of convolutional markings (gyral impressions on the inner table of the skull) seen throughout the skull vault. The primary cause may be raised intracranial pressure.…”
Section: Radiographic Examinationmentioning
confidence: 99%
“…DISCUSSION CASE REPORT Mishra S et al: Perceptive Anamnesis of Syndromic Craniosynostosis with Case Series of Crouzon Syndrome https://doi.org/10.38110/ijohmr.2020.v07i01.003atleast 20% of all cases [9][10][11][12][13][14][15][16]. In 1993, Jabs et al were the first to chronicle the genetic origin of syndromic craniosynostosis.…”
mentioning
confidence: 99%